Protein extraction and two‐dimensional gel electrophoresis of proteins in the marine mussel Mytilus galloprovincialis: an important tool for protein expression studies, food quality and safety assessment. (29th November 2012) - Campos, Alexandre; Puerto, Maria; Prieto, Ana; Cameán, Ana; Almeida, André M; Coelho, Ana V; Vasconcelos, Vitor
Abstract Background Shellfish farming is an important economic activity that provides society with a valuable source of food. Analyses of the protein content and metabolism of shellfish are therefore of utmost importance to monitor the presence and effects of environmental contaminants in these organisms and also to assess food quality and authenticity. The aim of the present study was to compare different protein extraction protocols commonly used in two‐dimensional gel electrophoresis (2DE) research and select the most suitable for the analysis of gill and digestive gland proteomes from the marine mussel Mytilus galloprovincialis. Results High‐resolution protein separation was achieved by direct solubilisation of proteins from M. galloprovincialis tissues with urea (7 mol L−1), thiourea (2 mol L−1), CHAPS (40 g L−1), DTT (65 mmol L−1) and ampholytes (pH 4–7, 8 mL L−1). Subsequent protein identification from 2DE gels by MALDI‐TOF/TOF mass spectrometry revealed a high number of proteins with functions in cytoskeleton structure, dynamics and maintenance. Other proteins identified in the 2DE gels are involved in energy production and carbohydrate metabolism, metal transport, chaperones and stress response, cell signalling and regulation, proteolysis and protein transduction. Conclusion Important protein markers for contaminant and quality assessment of shellfish food products can be analysed using 2DE.© 2012 Society of Chemical Industry